Establishing a link between the chemical composition and biological activities of Gladiolus italicus Mill. from the Turkish flora utilizing in vitro, in silico and network pharmacological methodologies - Zengin, Gokhan; Cetiz, Mehmet Veysi; Abul, Nurgul; Gulcin, Ilhami; Caprioli, Giovanni; Piatti, Diletta; Mahomoodally, Mohamad Fawzi (Taylor & Francis Ltd, 2025)
Objectives: Five solvent extracts (n-hexane, ethyl acetate, ethanol, ethanol/water (70%), and water) of Gladiolus italicus Mill. from Turkey were evaluated for chemical and biological properties. Methods: Antioxidant activities, inhibitory properties against key enzymes involved in the etiology of chronic diseases were tested, as well as cytotoxic effects on different cell lines. Chemical characterization was also carried out to determine the most abundant compounds of each extract. Results: The highest total phenolic content (TPC) was observed in the water extract while highest TFC in ethanol/water extract. The most abundant compounds in the extracts were hyperoside (69041.06 mg kg(-1)), isoquercitrin (46239.49 mg kg(-1)), delphindin-3,5-diglucoside (42043.81 mg kg(-1)), myricetin (21486.61 mg kg(-1)), and kaempferol-3-glucoside (21199.76 mg kg(-1)). Molecular dynamic (MD) simulations confirmed the structural stability and dynamic conformational integrity of these complexes over a period of 100 ns. In network pharmacology, A total of 657 unique target genes were screened: 52 associated with programmed cell death-1 (PD-1), 85 with vascular endothelial growth factor receptor-2 (VEGFR2), and 130 with fibroblast growth factor receptor-2 (FGFR2), identifying crucial gene interactions for these proteins. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted, revealing significant interactions and pathways such as the advanced glycation end products (AGE) and their receptors (RAGE) signaling pathway in diabetic complications and T- helper 17 (Th17) cell differentiation, among others. This elucidation of complex networks involving key genes like AKT Serine/Threonine Kinase 1 (AKT1), MYC proto-oncogene (MYC), tumor protein 53 (TP53), Interleukin 6 (IL6), and tumor necrosis factor (TNF) provides a promising foundation for the development of targeted therapies in the treatment of non-communicable diseases. Conclusion: These results show that G. italicus could be a natural source of potent antioxidants and enzyme inhibitors which need to be further explored for the development of biopharmaceuticals.
Keywords: Gladiolus italicus; antioxidant; enzyme inhibitors; hyperoside; molecular dynamics; network pharmacology